ANALISIS IMPLEMENTASI RAHN, QARDH DAN IJARAH PADA TRANSAKSI GADAI EMAS PT. BANK SYARIAH INDONESIA - Muhammad Fahmi Hibatullah (JOURNAL SAINS STUDENT RESEARCH, 2024)
The study in this article will discuss the implementation of Rahn, qardh, Ijarah in gold pawn transactions at PT Bank Syariah Indonesia Sharia Financial Institutions (LKS) which includes understanding, legal basis, provisions and requirements related to qardh contracts and benefits. The study of implementation is a bank financing product that is based or has the principle of mutual help. However, this kind of financing service is less popular in the community. Facilitate and streamline community economic activities by explaining the concept, implementation and benefits of qardh for business actors. This research uses a literature study method, namely by collecting various appropriate reading sources, then using descriptive analysis by identifying from various reference sources both books, journals and websites. Findings in this study